2015
DOI: 10.1007/s12288-015-0530-5
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Hemorrhagic Cystitis in Allogeneic Hematopoietic Stem Cell Transplant Patient

Abstract: Post bone marrow transplant patients are susceptible to atypical infections, especially viral pathogens. The risk increases many folds in cases of allogeneic transplantation, which also receive GVHD prophylaxis. Viral pathogens like cytomegalovirus and herpes are the common ones encountered during follow-up period. However, in recent times there have been reports of a variety of disease manifestations of rare viruses like polyoma virus and adenovirus. These viral infections may play a crucial role in morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Patients suffering from cancer are at higher risk of acquiring viral infections like SARS-CoV-2 infection and are likely to develop more complications [64,65]. Patients with hematological malignancies, patients on active chemotherapy, neutropenic patients, and bone marrow transplant patients are significantly at a higher risk [66].…”
Section: Cancer Patients and Their Carementioning
confidence: 99%
“…Patients suffering from cancer are at higher risk of acquiring viral infections like SARS-CoV-2 infection and are likely to develop more complications [64,65]. Patients with hematological malignancies, patients on active chemotherapy, neutropenic patients, and bone marrow transplant patients are significantly at a higher risk [66].…”
Section: Cancer Patients and Their Carementioning
confidence: 99%
“…Based on similar studies and our experience, we believe that immunocompromised individuals like patients with active cancer, HIV, patients on steroids etc. hold a higher risk of having complications if they acquire viral infections like COVID-2019 (11)(12)(13)(14).…”
Section: Novel Coronavirus (2019-ncov): Update On 3 Rd Coronavirus Oumentioning
confidence: 99%
“…In contrast to Reis et al , targeted exon sequencing done by Kardos et al (12 cases) revealed genetic alterations (eg, microsatellite instability- MSH2 and MSH6) similar to colorectal cancer 14. Reis et al found 31% and 16% expression of RAS/RAF/PI3K and PD-L1, respectively, in their study sample thereby prompting the potential role of anti‐PD‐1/PD‐L1 and anti‐epidermal growth factor receptor (EGFR) targeted anti-tyrosine kinase inhibitor (TKI) therapy.Awareness of rare urological conditions especially oncological is extemely important for timely diagnosis and treatment 8 15 16…”
Section: Discussionmentioning
confidence: 99%